Extraction of Building Footprints from Different Unmanned Aerial Vehicle (UAV) Platforms - Ismail, Nabila; Nizam Tahar, Khairul (International Journal of Engineering and Technology, 2018)
The demand for map updating is increasing especially for developing countries. Therefore, rapid data acquisition of an urban area is needed. This study proposes unmanned platform as one of the solutions for rapid data acquisition to update the map for developing countries. The objective of this study is to perform the extraction of building footprints using fixed-wing unmanned aerial vehicle (UAV) and multi-rotor UAV. All images acquired from both UAVs were processed using different image matching algorithms to perform relative orientation. The building footprints were extracted based on different orthophoto results. The building footprints were evaluated in terms of area and length. The results show the area based matching method records the accurate result in term of area and length assessment which are about 13m2 and 1.4m respectively. The results also show the multirotor provides the accurate results compared to fixed wing platform. The outcome could be used for specific applications such as urban expansion changes and land cover change detection.Â Â